Queismo and dequeismo in Spanish: sociolinguistic and geolectal patterns - Paredes García, Florentino (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The presence or absence of the preposition in certain constructions gives rise to a case of syntactic variation under the phenomena of queismo and dequeismo. In this article, we try to determine, for the Spanish-speaking environment, which are the geolectal and sociolinguistic patterns that define these constructions in the spoken language. Numerous studies have dealt with these phenomena in different territories, but they have the disadvantage that the investigations have been based on data obtained by means of procedures that are not comparable and following methodologies that are often disparate, which makes it very difficult to draw conclusions. To overcome this disadvantage, comparable studies can be used, since they are based on corpora obtained with the PRESEEA methodology and use the same criteria in the coding of variables. On the basis of these studies, the article outlines the dialectal differences and the effect of macro-social factors on these usages.